Through parents’ eyes: Exploring parental involvement’s experiences on online learning - Somariah Fitriani; Yessy Yanita Sari (Institute of Advanced Engineering and Science, 2023)
The engagement of parents in their children’s education has been the subject of several studies for decades, but socio-cultural theories that highlight parents’ mentoring of their children’s social learning have received less attention. This semi structure interview study intended to explore parents’ experiences of their involvement on children online learning. The study was conducted to obtain the data from six parents whose children attended primary schools. The data garnered from online and offline interviewing were transcribed and then interpreted by employing thematic content analysis. The study revealed four themes including parents’ emotional state and parental burnout, technological awareness, pedagogical experiences and benefits of online learning from parents’ perspectives. This study underlines the value of parental cooperation in fostering children’s learning and lowering mothers’ stress levels, particularly in online learning due to the COVID-19 pandemic.